Effect of Heat-Moisture Treatment on Qualities of Gluten-Free Alkaline Rice Noodles from Various Rice Flour Varieties - Chutima Chaichaw; Onanong Naivikul; Masubon Thongngam (Agriculture and Natural Resources, 2011)
The effects of heat-moisture treatment (HMT) applied to various rice flour varieties on the quality of gluten-free alkaline rice noodles (gluten-free ARN) made from the rice flour varieties were investigated. Three rice varieties: Chai Nat 1 (CN 1), Khao Dawk Mali 105 (KDML 105) and Rice Division 6 (RD 6) containing 30.07, 17.35 and 3.92% amylose content, respectively, were modified by HMT. The HMT was applied to rice flour with 25 g/100 g moisture at 120 °C for 5 h. The changes in the physicochemical properties on the RVA paste viscosity, thermal properties and water-binding capacity of the HMT rice flours were determined. Applications of the HMT rice flour from the three varieties to blend with the native CN 1 rice flour (30.07% amylose) at 30, 40, 50, 60 and 70% affected the cooking quality, texture properties and sensory evaluation of the resultant gluten-free ARN. The cooking loss and firmness of the gluten-free ARN with 30% HMT-RD 6 rice flour were not significantly different from those of the gluten-free ARN with 30% HMT-KDML 105 rice flour. Sensory evaluation based on firmness, adhesiveness, flavor and overall liking of both rice noodles (from 30% HMT-RD 6 and 30% HMT-KDML 105 rice flour) also had higher scores than those of the gluten-free ARN made from other composite rice flours.